The Influence of Transformational Leadership and OCB (Organizational Citizen Behavior) on The Performance of PT Mekar Prana Indah Jakarta's Employees Mediated by Variable Work Innovative Behavior - Ekayanto, Pramono; Prasilowati, Sri Lestari (Jurnal Ilmiah Sumber Daya Manusia, 2023)
This study aims to analyze the Effect of Transformational Leadership and OCB (Organizational Citizen Behavior) on Employee Performance which is mediated by the variable Work Innovative Behavior carried out on employees of PT Mekar Prana Indah Jakarta. This research is a survey research using a questionnaire as an instrument and taken as many as 51 respondents who are employees of PT Mekar Prana Indah Jakarta using a simple random sampling method. Data collection was carried out by providing a list of questions to respondents using the Google form. This study uses analytical tools.